THE IMPLEMENTASI PENDIDIKAN KARAKTER DISIPLIN DALAM MEMBENTUK SIKAP TANGGUNG JAWAB SANTRI TPQ THORIQOTUL HUDA BUGANGAN WONOSOBO - Verra Safitri; Ngarifin Shidiq; Vava Imam Agus Faishal (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2023)
This study aims to (1) Know the Discipline Character Education Concept in Forming the Responsible Attitude of TPQ Thoriqotul Huda Bugangan Wonosobo Santri; (2) Knowing the Implementation of Discipline Character Education in Forming the Responsibilities of Santri TPQ Thoriqotul Huda Bugangan Wonosobo; (3) Knowing the Supporting and Inhibiting Factors in the Implementation of Discipline Character Education in Forming the Responsibilities of the Santri TPQ Thoriqotul Huda Bugangan Wonosobo. This study uses a qualitative research approach where the type of research is descriptive. The subjects of this study were the heads of institutions, religious teachers, and students. Data collection techniques using the method of observation, interviews, and documentation. Data validity checking technique uses source triangulation technique. The analysis technique used is data reduction technique, data presentation, verification and conclusion. The results show that: 1) the concept of implementing disciplinary character education in forming an attitude of responsibility is implemented with the concept of cultural discipline through three stages, namely planning, implementation and evaluation; 2) The implementation of disciplinary character education in forming an attitude of responsibility is realized through three forms, namely self-development, incorporating the value of disciplinary character in the learning process, as well as providing rules and habituation of disciplinary attitudes. In its implementation found supporting and inhibiting factors; 3) The supporting factors are: self-awareness, interest and motivation. While the inhibiting factors are: the surrounding environment and the attitude of parents who do not motivate and control their child's development.